Financial Preparedness And Retirement Planning Among Emplyees Provident Fund (Epf) Contributors - Goh, Yi Yuern (2022)
Established in 1951, the Employees Provident Fund scheme made it compulsory for Malaysian workforce to save for their retirement. However, many of the employee provident fund contributors found that their Employees’ Provident Fund (EPF) savings are not enough to sustain them through retirement. Thus, this study was conducted to identify factors that affect an EPF contributor's decision to have planned savings for retirement besides employee provident fund savings and to analyse factors that contribute to EPF contributor's financial preparedness for retirement. These constitutes the first two objectives of this study. In the third objective, the study uses descriptive statistical analysis to explore the relationship between socio-demographic characteristic and preferred retirement saving channels. A total of 500 questionnaires were administered to those working in Kuala Lumpur and Selangor area. The likelihood of having a personal retirement saving plan and the categories of retirement financial preparedness were analysed using Logistic regression model and Multinomial logistic model respectively.